Optimizing Shariah Bank Financing Portfolios: Efficient Contract Combinations in Indonesia - Hikmatul Aliyah; Nora Azmia; Gheny Syahdiany (Universitas Darussalam Gontor, 2024)
This research aims to optimize the financing efficiency of Shariah Commercial Banks (SCBs) in Indonesia through a portfolio analysis involving various types of financing contracts. The analytical method employed is Data Envelopment Analysis (DEA). The study focuses on 9 Shariah Commercial Banks in Indonesia, utilizing quarterly data from 2015 to 2020, resulting in a total of 216 samples. The research findings reveal that SCBs achieved the highest efficiency score of 0.99 when the proportions of murabahah, musyarakah, mudharabah, ijarah, and sukuk financing were 52.79%, 29.10%, 3.25%, 2.18%, and 12.69%, respectively. These results underscore the significant impact of the financing proportions under various contract types on SCBs' efficiency levels. The highest efficiency is attained when the financing portfolio is dominated by murabahah, particularly at a proportion of 52.79%, highlighting the crucial role of murabahah in achieving optimal efficiency.